Disease burden and attributable risk factors for chronic obstructive pulmonary disease in China, Japan, and South Korea: trends for 1990 to 2021 period and predictions for 2031 - Wang, Yifan; Zhu, Jingwen; Wang, Shaoqiang; Zhou, Jihong (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a key public health concern in East Asia. China, Japan, and South Korea represent important regions in East Asia, and the three countries have various similarities in terms of culture, economic development models, and population structure. Therefore, understanding the COPD burden in these three countries is crucial for the prevention and management of COPD in East Asian.MethodsAge-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized mortality rate (ASMR), age-standardized disability-adjusted life rate (ASDR), age-period-cohort (APC) analysis, and Bayesian age-period-cohort (BAPC) analysis data of COPD in China, Japan, and South Korea were collected and determined using the GBD (Global Burden of Disease) 2021 database.ResultsChina had the highest COPD burden between 1990 and 2021, followed by South Korea, and Japan. The dominant risk factor related to mortality rates and DALYs was environmental/occupational risks in China, whereas behavioral risks in Japan and South Korea were more significant. BAPC predictions indicated that the ASIR, ASPR, and ASDR for COPD in China, Japan, and South Korea would exhibit a downward trend between 2021 and 2031. However, the trend of the age-standardized mortality rate (ASMR) would vary among the three countries.ConclusionUnder the influence of environmental conditions, the aging population, economic development trends, and the construction of medical security systems, China, Japan, and South Korea share commonalities as well as differences in terms of COPD burden. China’s actions concerning environmental protection have been effective, although reducing smoking rates and alleviating the pollution caused by industrialization are crucial for further reducing the COPD burden in China. Owing to Japan’s environmental protection policies, low smoking rates, and comprehensive social security measures, the COPD burden in Japan is relatively low compared to that in China and South Korea. Owing to the impact of environmental pollution, imperfections in the medical security system, and the influence of South Korea’s handling of related issues after the economic rise of the nation, the COPD burden in South Korea has undergone significant fluctuations.